PERAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENINGKATAN KUALITAS PENDIDIKAN - Victorynie, Irnie; Listiowati, Listiowati; Sidqia, Fanny; Dimyati, Mochamad (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Human resource development (HRD) in the education sector plays a crucial role in improving the quality of education in Indonesia. This study aims to explore the role of human resource development in enhancing the quality of education at an educational institution. The scope of the research includes training and development programs conducted at the institution, as well as their impact on the performance of teaching staff and the quality of teaching. The method used is a qualitative approach, where data is obtained through in-depth interviews and observations with several managers and teaching staff. The results of the study show that systematic human resource development programs, including training and teaching skill improvement, can enhance the quality of teaching and student satisfaction. Furthermore, improving human resource quality also contributes to the development of programs more aligned with the needs of the times. The conclusion of this research indicates that sustainable human resource development plays a key role in creating better quality education that meets the demands of modern society.